EVALUASI KEBIJAKAN BADAN SIBER DAN SANDI NEGARA DALAM PENANGGULANGAN BERITA HOAKS DI RANAH POLITIK SIBER TAHUN 2021(STUDI KASUS: Peraturan BSSN Nomor 3 Tahun 2021 Tentang Penyelenggaraan Literasi Media Dan Literasi Keamanan Siber) - Nebula Fauzan Hasani (2023)
This study aims to examine the policy evaluation of BSSN policies regarding their implementation and countermeasures to hoax news in the cyberspace, especially in the area of cyber politics by using public policy theory, policy formulation theory, implementation, evaluation theory, elite theory, and stakeholder mapping theory. This research uses a case study research approach with mixed methods. The mixed method in question is the use of qualitative and quantitative methods in reviewing the case studies studied. The method used in this study is a case study research approach associated with the BSSN as an object. The study obtained primary and secondary data. The sampling technique used in this study was purposive sampling. The author used systematic literature review technique, unobstrusive observation method, Normative Survey Method, and SWOT analysis. The result shows that despite BSSN specifically does not aim or is involved in the domain related to hoax countermeasures, as a governmental institution that maintains the security of cyberspace in Indonesia, it is still involved in hoax countermeasures. BSSN hopes that their policies related to mitigating hoaxes will be more massively implemented in order to effectively reduce the spread of hoaxes as BSSN also plays a role in keeping cyberspace free from hoaxes. BSSN has cooperated with other institutions related to hoax countermeasures such as building coordination patterns (i.e., common programs) between ministries as stakeholders. Although BSSN does not specifically build resources and infrastructure for hoax countermeasures, it still conducts hoax countermeasures such as media literacy to the public and clarifying hoax news that hit BSSN directly. It was found that the policies implemented by BSSN have no political interests. Based on the community's response to the BSSN policy, an IFAS score of 2.97 and an EFAS score of 3.28 were found respectively.